The complete mitochondrial genome of Amorphophallus albus and development of molecular markers for five Amorphophallus species based on mitochondrial DNA - Shan, Yuanyu; Li, Jingling; Zhang, Xue; Yu, Jie (Frontiers in Plant Science, 2023)
Introduction Amorphophallus albus is an herbaceous, cormous, perennial plant used as a food source and traditional medicine in Asia. Methods In this study, we assembled and annotated the complete mitochondrial genome (mitogenome) of A. albus. Then we analyzed the repeated elements and mitochondrial plastid sequences (MTPTs), predicted RNA editing sites in mitochondrial protein-coding genes (PCGs). Lastly, we inferred the phylogenetic relationships of A. albus and other angiosperms based on mitochondrial PCGs, and designed two molecular markers based on mitochondrial DNA. Results and discussion The complete mitogenome of A. albus consists of 19 circular chromosomes. And the total length of A. albus mitogenome is 537,044 bp, with the longest chromosome measuring 56,458 bp and the shortest measuring 12,040 bp. We identified and annotated a total of 36 protein-coding genes (PCGs), 21 tRNA genes, and 3 rRNA genes in the mitogenome. Additionally, we analyzed mitochondrial plastid DNAs (MTPTs) and identified 20 MTPTs between the two organelle genomes, with a combined length of 22,421 bp, accounting for 12.76% of the plastome. Besides, we predicted a total of 676 C to U RNA editing sites on 36 protein-coding genes of high confidence using Deepred-mt. Furthermore, extensive genomic rearrangement was observed between A. albus and the related mitogenomes. We conducted phylogenetic analyses based on mitochondrial PCGs to determine the evolutionary relationships between A. albus and other angiosperms. Finally, we developed and validated two molecular markers, Ai156 and Ai976, based on two intron regions (nad2i156 and nad4i976) respectively. The discrimination success rate was 100 % in validation experiments for five widely grown konjac species. Our results reveal the multi-chromosome mitogenome of A. albus, and the developed markers will facilitate molecular identification of this genus.